Applicability of a Polymerized Ionic Liquid/Carbon Nanoparticle Composite Electrolyte to Reductive Cyclization and Dimerization Reactions. (1st April 2016) - Herold, Sebastian; Waldvogel, Siegfried R.; Little, R. Daniel; Yoo, Seung Joon
Graphical abstract: Highlights: Reductive cyclization is conducted using composite dispersion of polymerized ionic liquid and carbon nanoparticles serving as a supporting electrolyte. Tedious isolation procedure is bypassed entirely, and ca. 93% recovery of the composite electrolyte is achieved via filtration. Slower electrohydrocyclization leading to a 6-membered ring allows time for the polymeric cation portion of the PIL to compete with the substrate for access to the cathode. An increase in the weight percentage of carbon nanoparticles leads to an increase in the surface area of the electrode, allowing access by the substrate with the attendant improvement in product yield. Abstract: Recently, a reusable polymerized ionic liquid/carbon nanoparticle composite electrolyte was developed and effectively applied to a variety of oxidative transformations. The efficient recovery of the composite material and its application in subsequent electroorganic conversions without sacrificing yield adds to the sustainability of the protocol. Herein, we describe our efforts to expand the operational window of the composite electrolyte to include cathodically initiated processes occurring at potentials up to −2.6 V. The results indicate that the composite electrolyte is applicable to reductive processes, but the scope of transformations appears to be limited.